EFFECTIVENESS OF THE USE OF LEARNING MODEL CONTROVERSIAL ISSUES (CI) ON CRITICAL THINKING ABILITY - Edo Dwi Cahyo; Laila Kodariyati (UNIVERSITAS PAKUAN, 2018)
This research is motivated by the low ability of students to think critically. The purpose of the study was to determine the effect of the Controversial Issues (CI) learning model in improving students' critical thinking skills. This study uses a quantitative approach with a quasi-experimental method. The study design used Nonequivalent [Pre-Test and Post-Test] Control Groups Design (NCGD). The research samples were fourth grade students of SDN 4 Metro Timur, SDN 5 Metro Timur, SDN 8 Metro Timur, and SDN 10 Metro Timur, 60 students were used as the experimental class and 60 students were used as the control class. Data collection tools in the form of sheets about students' critical thinking skills. Data collection techniques in the form of tests, namely pretest to measure the initial ability of students' critical thinking skills and posttest to see the final ability. Based on the results of the study concluded that the effectiveness of the use of the Controversial Issues learning model affects the critical thinking skills of class IV elementary school students, so that students' critical thinking skills in the experimental class are much better when compared to the control class that has conventional learning. Keywords: Controversial Issues, learning model, Social Skills.